A Novel BiOBr/CAU‐17 Composite with Enhanced Photo‐Catalytic Performance for Dye Degradation and Removal of Tetracycline Antibiotic Under Visible Light - Mansoor Akhtar; Shifa Ullah Khan; Ghulam Mustafa; Muhammad Ahmad; Tansir Ahamad (ChemistryOpen)
Abstract In order to improve the low specific surface area and high recombinant light generation carriers of BiOBr, loading BiOBr onto suitable Metal Organic Frameworks (MOFs) is an effective strategy to unleash its efficient visible light response and intrinsic catalytic activity. In this study, using classic MOF CAU‐17 as a precursor, using a straightforward co‐precipitation technique, four BiOBr/CAU‐17 composites with distinct MOF contents values BCAU‐1, BCAU‐2, BC, AU‐3, and BCAU‐4 were created, and their photo‐catalytic characteristics were examined. The BCAU‐2 composite exhibited much higher photo‐catalytic degradation efficiency for Rhodamine B (RhB) and Tetracycline (TC) than the pristine materials, counter compositions, and early reported materials. XRD, SEM, TEM, XPS, and EDX results revealed the strong synergistic photo‐catalytic effect of BiOBr and CAU‐17. The photocatalytic degradation of TC was significantly enhanced by the BiOBr bimetal modification, with the 2 wt.% BiOBr/CAU‐17 nanocomposite achieving an 87.2 % degradation of TC and 82 % Total Organic Carbon (TOC) removal within 60 min. The high photo‐degradation efficiency of BCAU‐2 composite should be attributed to the efficient transfer of photo‐generated carriers at interfaces and the synergistic effect between BiOBr/CAU‐17. Furthermore, the experiments on the capture of the active species proved that the main active free radicals involved in the degradation of RhB and TC are attributed to the photo‐induced holes h+ and ⋅ O2− under visible light. The catalyst's efficacy is corroborated by the outcomes of photoluminescence spectroscopy and photo current response. This study offers a new understanding for the design of green synthesis schemes for photo‐catalytic dye degradation and removal of certain antibiotics from the aquatic environment.